The effect of flue gas contaminants on the CO2 electroreduction to formic acid. Issue 42 (December 2020) - Legrand, U.; Apfel, U.-P.; Boffito, D.C.; Tavares, J.R.
Graphical abstract: Highlights: CO2 electroreduction to formic acid on Cu, Sn and Pb in 2- and 3- compartment cell. Identification of the main flue gas contaminants: N2, O2, H2 O, CO, NO2, SO2, PM, HC. O2 and SO2 are the most detrimental contaminants in CO2 to formic acid reduction. Abstract: Contaminants in an electrochemical cell converting CO2 to formic acid can lead to the deactivation of cathode catalysts through several pathways, causing severe performance loss over time. Potential contaminants from flue gas emissions of principal fossil fuels include N2, O2, H2 O, CO, NO2, SO2, particulate matter and hydrocarbons. Contaminant effects on the CO2 to formic acid electroreduction are scarcely covered in the literature. We describe in the present study these effects based on catalysts reported for the electroreduction of CO2 to formic acid, focusing principally on copper, tin and lead in the two most popular configurations, 2 and 3 compartment cells. Water solubility, metal affinity through chemisorption, known chemical reactions and altered electrochemical activities are the main focus of this review. We herein highlight that O2, SO2 and particulate matter have especially detrimental effects. While O2 can be efficiently removed from flue gas, additional treatment to remove SO2 and particulate matter is required. Our conclusions should raise interest in experimentally validating the effect of such contaminants.